2011
DOI: 10.7742/jksr.2011.5.5.267
|View full text |Cite
|
Sign up to set email alerts
|

A study on the impact of Professional burnout and job autonomy on turnover intention in radiologic technologists

Abstract: The purpose of this study was to examine the impact of the professional burnout and job autonomy of radiologic technologists on their turnover intention in hospitals. The major findings of the study were as follows: As for the average and standard deviation of the radiologic technologists in professional burnout and job autonomy, they got a mean of 3.15 in overall professional burnout, which was above the average. They got 2.88 in job autonomy, which was below the average. And they got 3.30 in turnover intenti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 0 publications
1
0
0
Order By: Relevance
“…Thus, police personnel’s feelings about their organization are impacted by their level of job autonomy relative to controlling and scheduling their work. This finding is consistent with the previous studies conducted in developed countries, which revealed that job autonomy negatively relates to turnover intention (Avanzi et al , 2014; Ghosh et al , 2013; De Neve and Devos, 2017; Hwang and Jeong, 2011; Rathi and Lee, 2017). This may also be attributed to the extent to which police personnel in the UAE are given the degree of freedom in determining how they should perform a job as suggested by Hackman and Oldham (1976).…”
Section: Resultssupporting
confidence: 93%
“…Thus, police personnel’s feelings about their organization are impacted by their level of job autonomy relative to controlling and scheduling their work. This finding is consistent with the previous studies conducted in developed countries, which revealed that job autonomy negatively relates to turnover intention (Avanzi et al , 2014; Ghosh et al , 2013; De Neve and Devos, 2017; Hwang and Jeong, 2011; Rathi and Lee, 2017). This may also be attributed to the extent to which police personnel in the UAE are given the degree of freedom in determining how they should perform a job as suggested by Hackman and Oldham (1976).…”
Section: Resultssupporting
confidence: 93%